The alkyne-tag Raman imaging of coronatine, a plant pathogen virulence factor, in Commelina communis and its possible mode of action - Ueda, Minoru; Hayashi, Kengo; Egoshi, Syusuke; Ishimaru, Yasuhiro; Takaoka, Yousuke; Yamakoshi, Hiroyuki; Dodo, Kosuke; Sodeoka, Mikiko (Organic & biomolecular chemistry, 2018)
We previously reported that coronatine, a virulence factor of plant bacteria, facilitates bacterial infection through an ER (endoplasmic reticulum)-mediated, non-canonical mechanism in the model dicot plant, Arabidopsis thaliana . Here, we report that this same ER-mechanism is ubiquitous among dicots and monocots, and works by affecting the ethylene signaling pathway widely found in plants. The subcellular localization of coronatine by the alkyne-tag Raman imaging (ATRI) approach provided a convincing clue.